Prenatal Administration of Betamethasone Causes Changes in the T Cell Receptor Repertoire Influencing Development of Autoimmunity - Gieras, Anna; Gehbauer, Christina; Perna-Barrull, David; Engler, Jan Broder; Diepenbruck, Ines; Glau, Laura; Joosse, Simon A.; Kersten, Nora; Klinge, Stefanie; Mittrücker, Hans-Willi; Friese, Manuel A.; Vives-Pi, Marta; et al. (Frontiers in Immunology, 2017)
Prenatal glucocorticoids are routinely administered to pregnant women at risk of preterm delivery in order to improve survival of the newborn. However, in half of the cases birth occurs outside the beneficial period for lung development. Glucocorticoids are potent immune modulators and cause apoptotic death of immature T cells and we have previously shown that prenatal betamethasone treatment at doses eliciting lung maturation induce profound thymocyte apoptosis in the offspring. Here, we asked if there are long-term consequences on the offspring’s immunity after this treatment. In the non-obese diabetic (NOD) mouse model, prenatal betamethasone clearly decreased the frequency of pathogenic T cells and the incidence of type 1 diabetes (T1D). In contrast, in the lupus-prone MRL/lpr strain, prenatal glucocorticoids induced changes in the T cell repertoire that resulted in more autoreactive cells. Even though glucocorticoids transiently enhanced regulatory T cell (Treg) development, these cells did not have a protective effect in a model for multiple sclerosis which relies on a limited repertoire of pathogenic T cells for disease induction that were not affected by prenatal betamethasone. We conclude that prenatal steroid treatment, by inducing changes in the TCR repertoire, has unforeseeable consequences on development of autoimmune disease. Our data should encourage further research to fully understand the consequences of this widely used treatment.